Laparoscopic assisted submucosal excision of an intussuscepting colonic lipoma - Ejtehadi, Farshid (J Surg Case Rep, 2020)
Colonic lipomas are the most widespread non-epithelial tumours of the large bowel. They often present with absent, non-specific or intermittent symptoms. Intussusception is the most common complication that may occur as a result of such a lesion. We present the case of a young female patient with a history of intermittent abdominal pain associated with nausea. She presented to the emergency department with subacute large bowel obstruction. A diagnosis of colo-colic intussusception due to a large descending colonic lipoma was confirmed on CT scan. The patient underwent a laparoscopic assisted submucosal excision of the lipoma. We discuss this unique operative technique as well as preoperative investigations and histopathology findings. Although successful endoscopic excision of lipomas has been reported, segmental resection of the colon is most commonly practiced. To the best of our knowledge, this is the first report of laparoscopic assisted submucosal excision of an intussuscepting colonic lipoma.